Use of lipid lowering drugs for primary prevention of coronary heart disease: meta-analysis of randomised trials. Issue 7267 (21st October 2000) - Pignone, Michael; Phillips, Christopher; Mulrow, Cynthia
Abstract: Objective: To summarise the effect of primary prevention with lipid lowering drugs on coronary heart disease events, coronary heart disease mortality, and all cause mortality. Design: Meta-analysis. Identification: Systematic search of the Medline database from January 1994 to June 1999 for English language studies examining drug treatment for lipid disorders (use of the MeSH terms "hyperlipidemia" and "anticholesteremic agents, " keyword searches for individual drug names, and a search strategy for identifying randomised trials to capture relevant articles); identification of older studies through systematic reviews and hand search of bibliographies. Inclusion criteria: All randomised trials of at least one year's duration that examined drug treatment for patients with no known coronary heart disease, cerebrovascular disease, or peripheral vascular disease and that measured clinical end points, including all cause mortality, coronary heart disease mortality, and non-fatal myocardial infarctions. Data extraction: Review of the articles and extracted relevant data by two authors separately, with disagreements resolved by consensus. Results: Four studies met eligibility criteria. Drug treatment reduced the odds of a coronary heart disease event by 30% (summary odds ratio 0.70, 95% confidence interval 0.62 to 0.79) but not the odds of all cause mortality (0.94, 0.81 to 1.09). When statin drugs were considered alone, no substantial differences in results were found. Conclusions: Treatment with lipid lowering drugs lasting five to seven years reduces coronary heart disease events but not all cause mortality in people with no known cardiovascular disease.